2016
DOI: 10.5539/jas.v8n3p64
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Value of Sweet Potato Tubers [Ipomoea batatas (L.) Lamb.] Consumed by Infants and Children of Dani Tribe in Kurulu District, Baliem-Jayawijaya

Abstract: Sweet potato is an important staple food crop especially for the local people of Central Highlands Jayawijaya. There are many accessions that have always been maintained their existence to enrich the types of consumption. Traditionally, sweet potato accessions were grouped based on the utilization, such as for animal feed, cultural ceremonies, consumption for adults, as well as for children and infants. This study was aimed to analyze the nutritional value of sweet potatoes consumed by infants and children of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
4
4
0
1
Order By: Relevance
“…The sweet potato roots analysed in the present study contained 1.68% of fat, which is in agreement with 1.62% reported previously [14]. In general, sweet potato roots are low in fat [7]. The fat content of amaranth leaves analysed in the present study revealed 7.89%.…”
Section: Fat Contentsupporting
confidence: 92%
See 3 more Smart Citations
“…The sweet potato roots analysed in the present study contained 1.68% of fat, which is in agreement with 1.62% reported previously [14]. In general, sweet potato roots are low in fat [7]. The fat content of amaranth leaves analysed in the present study revealed 7.89%.…”
Section: Fat Contentsupporting
confidence: 92%
“…All these results revealed that red kidney beans grown in Rwanda are rich in protein and the traditional processing methods did not affect the protein content. Sweet potato roots are poor in protein and they contained 6.66% in the present study [7]. A similar study reported that protein content in sweet potato roots was in the range of 1.73-9.14% on a dry weight basis and of good quality [21], which confirms the present results.…”
Section: Protein Contentsupporting
confidence: 88%
See 2 more Smart Citations
“…Its rusticity guarantees resistance to drought, little demand on nutrients and advantageous competition with weeds, for quickly covering the soil. In addition, to use in human food, sweet potatoes can be used in animal feed and ethanol production (Corrêa et al, 2016;Silva, Almeida, Alvim-Ferraz, & Dias, 2018;Suparno, Prabawardani, & Pattikawa, 2016;Vizzotto, Pereira, Castro, Raphaelli, & Krolow, 2017).…”
Section: Introductionmentioning
confidence: 99%